Neuronal CTGF/CCN2 negatively regulates myelination in a mouse model of tuberous sclerosis complex - Ercan, Ebru (J Exp Med, 2017)
Disruption of myelination during development has been implicated in a range of neurodevelopmental disorders including tuberous sclerosis complex (TSC). TSC patients with autism display impairments in white matter integrity. Similarly, mice lacking neuronal Tsc1 have a hypomyelination phenotype. However, the mechanisms that underlie these phenotypes remain unknown. In this study, we demonstrate that neuronal TSC1/2 orchestrates a program of oligodendrocyte maturation through the regulated secretion of connective tissue growth factor (CTGF). We characterize oligodendrocyte maturation both in vitro and in vivo. We find that neuron-specific Tsc1 deletion results in an increase in CTGF secretion that non–cell autonomously stunts oligodendrocyte development and decreases the total number of oligodendrocytes. Genetic deletion of CTGF from neurons, in turn, mitigates the TSC-dependent hypomyelination phenotype. These results show that the mechanistic target of rapamycin (mTOR) pathway in neurons regulates CTGF production and secretion, revealing a paracrine mechanism by which neuronal signaling regulates oligodendrocyte maturation and myelination in TSC. This study highlights the role of mTOR-dependent signaling between neuronal and nonneuronal cells in the regulation of myelin and identifies an additional therapeutic avenue for this disease.